New potential antitumoral fluorescent tetracyclic thieno[3,2-b]pyridine derivatives: interaction with DNA and nanosized liposomes - Castanheira, Elisabete M. S. (2011)
Fluorescence properties of two new potential antitumoral tetracyclic thieno[3,2-b]pyridine derivatives were studied in solution and in liposomes of DPPC (dipalmitoyl phosphatidylcholine), egg lecithin (phosphatidylcholine from egg yolk; Egg-PC) and DODAB (dioctadecyldimethylammonium bromide). Compound 1, pyrido[2',3':3,2]thieno[4,5-d]pyrido[1,2-a]pyrimidin-6-one, exhibits reasonably high fluorescence quantum yields in all solvents studied (between 0.20 and 0.30), while for compound 2, 3-[(p-methoxyphenyl)ethynyl]pyrido[2',3':3,2]thieno[4,5-d]pyrido[1,2-a]pyrimidin-6-one, the values are much lower (between 0.01 and 0.05). The interaction of these compounds with salmon sperm DNA was studied using spectroscopic methods, allowing the determination of intrinsic binding constants, Ki = (8.7 ± 0.9) x 10^3 M^-1 for compound 1 and Ki = (5.9 ± 0.6) x 10^3 M^-1 for 2, and binding site sizes of n = 11 ± 3 and n = 7 ± 2 base pairs, respectively. Compound 2 is the most intercalative compound in salmon sperm DNA (35%), while for compound 1 only 11% of the molecules are intercalated. Studies of incorporation of both compounds in liposomes of DPPC, Egg-PC and DODAB revealed that compound 2 is mainly located in the hydrophobic region of the lipid bilayer, while compound 1 prefers a hydrated and fluid environment.